Los desechos hospitalarios y su manejo eficiente en los hospitales públicos, caso de estudio, hospital del MSP, “Hospital Sagrado Corazón de Jesús”, del cantón Quevedo - Rodríguez Rivera, Luzmila Mercedes (2015)
The research topic was held at the Sacred Heart of Jesus Hospital, located in the urban parish October 7 Cantón Quevedo, Los Rios Province; starting with an introduction, a general objective: Design a management manual storage and disposal of hospital waste, the Sacred Heart of Jesus Hospital, the Quevedo Canton, Province de los Rios, Year 2014; Specific objectives a) Conduct an assessment of working conditions made in the handling of waste Quevedo Canton Hospital Sacred Heart of Jesus, b) Identify techniques of separation, collection, storage and disposal of hospital waste and compliance legal provisions for proper treatment of hospital waste, and c) establish the model of a management manual for handling hospital waste in the Sacred Heart of Jesus Hospital Quevedo Canton; location of the Sacred Heart of Jesus Hospital Quevedo Canton, materials and methods, research techniques, the share of Personal Health of HSCJ, who were applied the survey population, and an interview was determined by Dr. Ephraim Ubilla Zamora , Director of the Hospital. The objectives were developed, and through interviews and surveys the provision of information for both the analysis of the current situation was achieved by identifying and obtaining separation techniques, collection, storage and disposal of hospital waste and compliance of the provisions, then define the model proposed management manual for handling hospital waste in the Sacred Heart of Jesus Hospital Quevedo Canton. In conclusion it was determined that there was only HSCJ in the manual provided by the Ministry of Public Health; and based on it and other similar structure proposed for implementation manual it was updated; as evidence accompanying the instrument used in the survey and photographs that attest to the performance in research, contributing to the principles of Good Living.